O veto presidencial no STF: estudo de um caso de tensão entre os poderes - Bispo, Nikolay Henrique (2016)
This study aims at describing and analyzing how the Supremo Tribunal Federal (STF) rules the cases that deal with presidential veto, in order to identify how the STF's relationship with the legislative and executive branches is built. Through the cases, this research focus on the rules established by the STF in defining the role of the executive and legislative to decide cases on the presidential veto and in limiting its own jurisdiction. To this, the author develops a theoretical reasoning about the judiciary's role in this phase of the separation of powers (veto); and analyzes fifty-five decisions of the Supreme Court on the subject, several legislative branch documents on bills and laws and, finally, presidential documents that have reasoning for the presidential veto. The cases studied showed that the form of the Supreme Court decision in such cases is diverse, since it is possible to identify profiles for each of the seven groups of cases created in the research. Secondly, I found that the cases analyzed, as a rule, represent a breach of understanding about the political decision-making among political actors involved and STF is demanded to solve the conflicts. The cases also showed that the Supreme Court is clear on the scope of their responsibilities for the control of such cases, allowing ample space for its own power, however, in practice only in exceptional cases this body decides invalid (unconstitutional) the case. I also concluded that, even if exceptional cases where the Supreme Court acts in an emphatic manner, the consequences of these decisions can cause are serious and that therefore there should be legal limits to its performance and even accountability for their decisions. Finally, the scholars of separation of powers, more specifically the veto, do not analyze the importance that the judiciary has in this process.